(untitled) (Research, Society and Development, 2021)
In view of the role of the press, which influences government agendas and public policies, it is important to understand its role in the construction of the social imaginary when publishing content related to the Homeless Population. Objective: to analyze the press speeches about the Homeless People in the media in the light of Perseu Abramo’s Great Press Manipulation Standards. This is a documentary research with a qualitative approach that used in the data collection the search on the internet for the terms: homeless people, beggars and Population in Street Situation, with time delimitation from 2014 to 2019. 5 documents were identified that contained 9 terms, totaling 29 repetitions. The material was submitted to Bardin’s content analysis, emerging the category "nomenclature for Homeless person and the use of psychoactive substances". The discussion identified a homogenizing discourse on the ways of living on the street, which links this group to the use of psychoactive substances, in a stigmatizing way, reinforcing social exclusion. It concludes by the need to rethink the involvement of the media in maintaining the neoliberal status quo, in perpetuating violence and making this diverse and complex group invisible.